Identifying indigenous practices for cultivation of wild saprophytic mushrooms: responding to the need for sustainable utilization of natural resources - Wendiro, Deborah; Wacoo, Alex Paul; Wise, Graham (Journal of Ethnobiology and Ethnomedicine, 2019)
Due to increasing pressure on natural resources, subsistence agriculture communities in Uganda and Sub-Saharan Africa are experiencing increasingly restricted access to diminishing natural resources that are a critical requirement of their livelihoods. Previously, common-pool resources like forests and grasslands have been either gazetted for conservation or leased for agriculture, the latter in particular for large-scale sugarcane production. Satisfying the increasing consumer demand for grassland or forestry products like wild mushrooms as food or medicine, requires innovative ethno-biological and industry development strategies to improve production capacity, while easing the pressure on diminishing natural resources and averting ecosystems degradation. Methods: This case study addresses traditional knowledge systems for artisanal mycoculture to identify cultivation practices that enhance sustainable utilization of natural resources. Multi-scalar stakeholder engagement across government and community sectors identified artisanal mushroom producers across five districts in Uganda. Focus groups and semi-structured interviews characterized artisanal production methods and identified locally used substrates for cultivation of different mushroom species. Results: Artisanal practices were characterized for the cultivation of six wild saprophytic mushroom species including Volvariella speciosa (akasukusuku), two Termitomyces sp. (obunegyere and another locally unnamed species), Agaricus sp. (ensyabire) and Agrocybe sp. (emponzira), and one exotic Pleurotus sp. (oyster) that are used as food or medicine. The substrates used for each species differed according to the mushroom’s mode of decomposition, those being the following: tertiary decomposers such as those growing under rotting tree stumps or logs from forestry activity like the Agrocybe sp. known as emponzira which grows in forests, thickets, or near homesteads where big logs of hardwood have been left to rot. Also pieces of firewood are chipped off whenever need arises thus providing fuel; secondary decomposers growing on naturally composted grass associated with termites like the Termitomyces sp. known as obunegyere growing in protected sites in gardens, composted cattle manure for Agaricus sp. known as ensyabire in the kraal area where cattle manure is plenty, composted maize cobs for a locally unnamed Agaricus sp. on heaped cobs placed near homesteads; and primary decomposers growing on waste sorghum from brewing the traditional alcoholic drink, muramba for Pleurotus sp. (oyster), and banana and spear grass residue from banana juice processing like the Volvariella speciosa known as akasukusuku because it is associated with the banana plantation locally known in the Luganda language as olusuku and is usually heaped under ficus trees. Management practices also varied based on mode of decomposition and other ecological requirements such as the following: zero tillage and minimal disturbance in areas where obunegyere grow, heaping banana and spear grass residues under the cool ficus trees which also keep them away from banana stump that may cause infestation with nematodes and insects. Even within the generic practices accessibility by the users is critical for example placing logs near homes where children can use them to play, they can be used as fire wood and to even get off-season mushroom as household waste water can make the mushrooms grow. Conclusions: Our description of artisanal mycoculture methods that respond to conservation and utilization pressures, demonstrates the value of addressing traditional knowledge to improve ethno-biology and mycoculture industry practice. Traditional communities engage in multiple technological and organizational innovations and practices for sustainability and in the case of mushroom production to conserve the environment and culture, ensure variety, food and nutrition security, and income. The results of this study present opportunities to preserve ecosystem quality while developing an artisanal mycoculture system. They have also identified aspects of artisanal mycoculture that most urgently require further ethno-biological study and industry development. Future research and industry development can utilize the result of this study to boost artisanal production of wild saprophytic mushrooms in Sub-Saharan countries, for food or medicinal consumption, and environment conservation. Further development of production efficiencies in context with sustainable natural resource management is recommended.
Keywords: Industry development; Wild saprophytic mushrooms; Edible mushrooms; Medicinal mushrooms; Traditional knowledge; Artisanal production; Natural resources management; Conservation; Sustainable development; Mushroom substrates